Analysis of clinical records of dental patients attending Jordan University Hospital: Documentation of drug prescriptions and local anesthetic injections - Najla Dar-Odeh; Soukaina Ryalat; Mohammad Shayyab; Osama Abu-Hammad (Dove Medical Press, 2008)
Najla Dar-Odeh1, Soukaina Ryalat1, Mohammad Shayyab1, Osama Abu-Hammad21Department of Oral and Maxillofacial Surgery Oral Medicine and Periodontics, Faculty of Dentistry, University of Jordan, Jordan; 2Department of Prosthetic Dentistry, Faculty of Dentistry, University of Jordan, JordanObjectives: The aim of this study was to analyze clinical records of dental patients attending the Dental Department at the University of Jordan Hospital: a teaching hospital in Jordan. Analysis aimed at determining whether dental specialists properly documented the drug prescriptions and local anesthetic injections given to their patients.Methods: Dental records of the Dental Department at the Jordan University Hospital were reviewed during the period from April 3rd until April 26th 2007 along with the issued prescriptions during that period.Results: A total of 1000 records were reviewed with a total of 53 prescriptions issued during that period. Thirty records documented the prescription by stating the category of the prescribed drug. Only 13 records stated the generic or the trade names of the prescribed drugs. Of these, 5 records contained the full elements of a prescription. As for local anesthetic injections, the term “LA used” was found in 22 records while the names and quantities of the local anesthetics used were documented in only 13 records. Only 5 records documented the full elements of a local anesthetic injection.Conclusion: The essential data of drug prescriptions and local anesthetic injections were poorly documented by the investigated group of dental specialists. It is recommended that the administration of the hospital and the dental department implement clear and firm guidelines for dental practitioners in particular to do the required documentation procedure.Keywords: dental records, documentation, prescriptions, local anesthesia